Score Faced y Score BSI como predictores de mortalidad en pacientes adultos con bronquiectasias - Zárate Espinoza, Eric Paúl (2019)
The impact of bronchiectasis on the individual suffering from it can be measured in different ways. As bronchiectasis is a multidimensional pathology, a single variable is unable to capture the severity of the disease and, above all, assess its prognosis. Thus, in an attempt to more fully assess the prognosis or severity of bronchiectasis, easy-to-use daily clinic scales have been developed in recent years, providing more accurate prognostic information. The objective of the work was to compare between the FACED and BSI scores the ability to predict mortality in adult patients with bronchiectasis. The study was observational, retrospective, in which 250 outpatients who had been diagnosed with bronchiectasis for five years with the Naidich criteria in TACAR and with a spirometry study were evaluated. Patients who also suffered from some degree of immunosuppression, diabetes mellitus, cystic fibrosis, COPD, pneumonia, sepsis, and patients diagnosed with bronchiectasis during hospitalization were not included in the study. The data was collected from the medical records and from the SINADEF platform. The collected data was organized in a database in the spss 24.0 program. The measures of absolute and relative frequency were determined, the risk was calculated for the factor studied using the Relative Risk (RR) test. Likewise, the ROC curve was obtained for each of the Scores, identifying the cut-off points for different Sensitivity and Specificity values of each forecast method, using values from the present investigation.